The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1953
DOI: 10.1161/01.res.1.3.230
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Progressive General Anoxia on the Pulmonary Circulation

Abstract: The effects of progressive anoxia on the hemodynamic changes in the pulmonary circuit were reinvestigated in anesthetized dogs. Evidence is presented that some increase in pulmonary arterial resistance takes place, but that the augmented output of the right ventricle is dominantly responsible for elevation of the pulmonary arterial pressure when anoxia affects the bodv as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1954
1954
1975
1975

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The fact that the 02 uptake consistently decreased when 15.65 per cent 02 was breathed is not understood but has been commonly observed to occur in this laboratory under resting conditions whether ventilation is controlled (21) or uncontrolled. It seems possible that in these three experiments the low 02 produced a change in the pulmonary vascular bed (22,23) so that all the conditions necessary for the valid calculation of Do2 may not have been satisfied. (Table I) were, however, not unusually large nor were their tidal volumes during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the 02 uptake consistently decreased when 15.65 per cent 02 was breathed is not understood but has been commonly observed to occur in this laboratory under resting conditions whether ventilation is controlled (21) or uncontrolled. It seems possible that in these three experiments the low 02 produced a change in the pulmonary vascular bed (22,23) so that all the conditions necessary for the valid calculation of Do2 may not have been satisfied. (Table I) were, however, not unusually large nor were their tidal volumes during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary pressor response to hypoxia was studied in each animal under three different circumstances: (1) with the animal awake, (2) in the anesthetized animal with intact pulmonary circulation in which changes in pulmonary vascular resistance could be calculated as in Group A, and (3) during constant flow perfusion of a portion of the pulmonary vasculature.…”
Section: Group Bmentioning
confidence: 99%
“…15 yr ago it was suggested that the catecholamines were involved in this response (1,2). Subsequent investigations have been inconclusive in either supporting or refuting this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The site of action of this vasomotor response has not been definitely identified. (7), Rahn and Bahnson (20), Hiirlimann and Wiggers (21), and Stroud and Conn (22). It has also been proposed that the vasomotor activity of the alveolar capillaries could be responsible for the hemodynamic changes that follow alterations in alveolar oxygen tension (4).…”
Section: Discussionmentioning
confidence: 99%